Myc and Skp2 overexpression promotes p27 ubiquitination and degradation in Ewing Sarcoma - Yuta Kubota; Masanori Kawano; Ichiro Itonaga; Nobuhiro Kaku; Kazuhiro Tanaka (PLoS ONE, 2026)
Background Ewing sarcoma remains partially uncontrollable even after treatment with chemotherapy, surgery, and radiation therapy due to its high malignancy. To explore genes that drive Ewing sarcoma cell proliferation, we conducted a comprehensive analysis of mRNA expression. Based on cDNA array results, we identified consistently elevated expression of Myc and S-phase kinase-associated protein 2 (Skp2) across all five Ewing sarcoma cell lines examined. Methods The functional roles of Myc and Skp2 were assessed by siRNA-mediated knockdown and overexpression assays, followed by cell proliferation, cell cycle, and protein expression analyses. Ubiquitination of p27 and activation of the CCNE/CDK2 complex were evaluated by immunoprecipitation and western blotting. Finally, the in vivo relevance of Myc and Skp2 knockdown was validated using a xenograft mouse model. Results Knockdown (KD) using siRNAs specific for Myc and Skp2 resulted in reduced cell growth and an increased proportion of cells in the G0/G1 phase, indicating G1 arrest. In KD cells, we observed decreased CDK2 activity, increased p27 expression, and reduced expression of cyclin E (CCNE). The increased activity of the CCNE/CDK2 complex led to enhanced phosphorylation of p27 at Thr187, accelerating p27 degradation via Skp2-mediated ubiquitination. Concurrently, the CCNE/CDK2 complex promoted phosphorylation of Rb at Ser807/808, which is involved in E2F1 activation. Conclusion This mechanism was identified through a comprehensive expression analysis aimed at uncovering the drivers of cell cycle acceleration in Ewing sarcoma. The findings offer new insights into therapeutic strategies for this malignancy, which has seen little progress in treatment over several decades. This discovery holds the potential to transform the current landscape, as no effective molecularly targeted therapies have yet been developed.